(untitled) (The Review of Diabetic Studies, 2025)
Background:Sarcoidosis is a chronic granulomatous condition that predominantly impacts the lungs and thoracic lymph nodes, characterized by noncaseating granulomas, though it can affect any organ system. Aim: This study aims to investigate the effect of alternative therapies (infliximab, and adalimumab) in the treatment of refractory sarcoidosis. Method This study aims to analyze data from patients diagnosed with sarcoidosis who received anti-TNF therapy (infliximab or adalimumab) for refractory disease at Al-Azhar Hospitals. Refractory sarcoidosis is defined as persistent or worsening disease activity despite optimal treatment with a minimum of two traditional immunosuppressive drugs. The study will include patients with a diagnosis confirmed by histology, age ≥ 18 years, documented refractory sarcoidosis, and treatment with infliximab or adalimumab for at least 3-6 months.Data collection included demographics, disease characteristics, prior treatments, anti-TNF therapy, dosage and frequency, duration of therapy, and concurrent medications. Outcome measures will include clinical response, radiological response, extrapulmonary sarcoidosis, laboratory parameters, and adverse events. Definitions of response include complete response, partial response, stable disease, and progressive disease.Statistical analysis will use descriptive statistics to characterize the study population and present baseline characteristics. The study was conducted with the ethical committee of research at Al-Azhar University. Results: The study compared three groups of patients with sarcoidosis, focusing on the use of immunomodulators, medication use, and extrapulmonary involvement. Results showed a gradual improvement in patients in group G1, with a decrease in dyspnea, cough, and fatigue, and improved respiratory capacity. Patients in Group 3 experienced slow improvement and deterioration, while those in the first group showed the greatest rates of improvement. The results highlight the effectiveness of biological therapies in controlling resistant sarcoidosis and achieving gradual and sustained improvement. Conclusion: Anti-TNF-α therapy, infliximab/adalimumab, outperforms standard treatment for refractory sarcoidosis, enhancing symptoms, lung function, and radiological results over 24 months, emphasizing the need for biological treatments.